Aspects of Public Expenditure Theories - Samuelson, Paul A. (The Review of Economics and Statistics, 1958)
ECONOMIC theorists have done work of high quality and great quantity in the field of taxation. Public expenditure seems to have been relatively neglected. To illustrate this, let me turn to Professor Pigou. I do so with some diffidence, remembering what Ralph Waldo Emerson said to Oliver Wendell Holmes when Holmes showed him a youthful criticism of Plato. When you strike at a King, Emerson said, sure you kill I have no wish to assassinate Professor Pigou. Nor even to criticize him. But immortality does have its price: if one writes an outstanding treatise such as Pigou's A Study in Public Finance, one must expect other men to swarm about it, picking a nugget here and probing for a weakness there. Of a book of some 285 pages, Pigou devotes most attention to taxes. At least 200 pages to taxes; of the rest, most are concerned with fiscal policy and its impact on the business cycle. What about the pure theory of public expenditure? I can find barely half a dozen pages devoted to the heart of this matter specifically, pages 30-34. And even if we widen the category to include Pigou's definitions of transfer and exhaustive expenditure and his discussion of pricing of state-operated public utilities we still cannot bring the total of pages much beyond twenty. Now it may be that this ratio of 200 on taxes to 20 on expenditure is the proper one. Perhaps there is really nothing much to say about expenditure, and so heavily overbalanced a page budget may be truly optimal. On the other hand, we must admit that fashion has a great influence in economics, which suggests that we ought periodically to survey the neglected areas of theory to make sure that they do deserve to be left in their underdeveloped and backward states. I have previously published (this REVIEW, xxxvi, November I 9 54, 3 8 7-89) some thoughts on public expenditure theory; and in order to widen the discussion among economic theorists, I later gave a non-mathematical exposition (ibid., XXXVII, November I955, 350-56). I do not propose here to give a detailed review of these theories. Rather, I'd like to think aloud about some of the difficulties with expenditure theory and with political decision-making. On these subjects, Richard Musgrave and Julius Margolis have done outstanding research and I must confess my obligation to them for much friendly counsel.